PEMBUATAN E-LIBRARY MADRASAH ALIYAH NEGERI (MAN) ARGA MAKMUR MENGGUNAKAN MACROMEDIA DREAMWEAVER 8 - Khairil, Khairil; Trianggana, Dimas Aulia; Yupianti, Yupianti (Jurnal Media Infotama, 2012)
Developing of technology information is very faster to influence in our and profesion, it can be makes change of system at development and factor change of the working way of them too. That is make we one more to increase librarian professional in technology skill to increase of the working way and library service.The purpose of the research is make MAN Arga Makmur library using to Macomedia Dreamweaver 8 e-library as a tool to manages organize of databse Mysql. The method of collceting with line observation about the book information in MAN Arga Makmur library interview, that is give some quisionaine to MAN Arga Makmur librarian. From the discussion, we are get the smmerize although mus suturaly MAN Arga Makmur library to increase technology information library with e-library, so the senue of information to become online pronidad.